2015
DOI: 10.4236/ajps.2015.67108
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Water Stress on the Growth and Yield of Cotton Crop (<i>Gossypium hirsutum</i> L.)

Abstract: Cotton is one of the most important fibre crops playing a key role in economic and social affairs of the world. Water is a critical factor which influences on growth and yield of the cotton crop. Scarcity of water has put tremendous pressure on scientists to introduce drought tolerant cotton varieties. This study was aimed to determine water stress effects on the growth and yield of cotton. The present study was carried out to examine the effect of number of irrigations on the growth and yield of cotton during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 4 publications
7
22
0
Order By: Relevance
“…Muttar [30] and Al-Khirllah [22] obtained same results, that two weekly irrigation interval gave the highest ginning percentage about 21.14%. But Lee et al, [34], Honey [31] and Sahito et al, [35] were found irrigation at 21 days (three weeks) had attained the highest ginning percentage about 33.86%. Associated increasing potassium levels significant increment of ginning percentage in both seasons.…”
Section: Ginning Percentagementioning
confidence: 99%
“…Muttar [30] and Al-Khirllah [22] obtained same results, that two weekly irrigation interval gave the highest ginning percentage about 21.14%. But Lee et al, [34], Honey [31] and Sahito et al, [35] were found irrigation at 21 days (three weeks) had attained the highest ginning percentage about 33.86%. Associated increasing potassium levels significant increment of ginning percentage in both seasons.…”
Section: Ginning Percentagementioning
confidence: 99%
“…Cotton is one of the most valuable crops for providing natural fibers for the textile industry globally. China, the United States, India, Pakistan, Uzbekistan, Turkey, and Brazil are the seven largest producers of cotton worldwide, while China, the United States, the Franc Zone of Africa, Uzbekistan, Australia, and India are the five leading exporters [ 42 ]. China, the United States, and India provide most of the world’s cotton; more than 15.95 million metric tons of cotton as lint and 29.26 million metric tons of cotton as seeds were exported in 2014 (FAOSTAT, ).…”
Section: Introductionmentioning
confidence: 99%
“…The productivity of cotton is detrimentally affected by biotic and abiotic stresses, such as fungi, harmful insects, drought, and soil salinity. Among abiotic stresses, drought was found to be the most serious stress that reduced cotton yields significantly at the experimental fields of the Agriculture Research Institute, Tandojam, Pakistan during the year 2007 [ 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…These decrease might be due to the increase in temperature and a reduced in water availability (Ahmed et al, 2017). Improved irrigation use and appropriate planning is a possible selection norm for increasing yield under drought stress and it assesses the method and depth of water applied, whether it was used at optimum level by a plant (Sahito et al, 2015). The major objective of applying the WD is to raise water use efficiency (WUE) by decrease the amount of water applied or by increase irrigation intervals (Semida et al, 2017).…”
Section: Introductionmentioning
confidence: 99%